(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1858)
The ancient mound at Castle Hill was destroyed during work on the great North of Scotland Railway. This article describes the discoveries made at the site during its removal including several large granite stones (at least two of which were inscribed with figures) and a number of small pits containing various materials. The article concludes with a letter from a local antiquarian about several cists and their contents that were uncovered near Kinaldy.